Rehabilitación cardíaca en adultos con desfibriladores automáticos implantados - Quisnia Gusqui, Katerine Elizabeth (2022)
ABSTRACT Cardiac rehabilitation is a physical training program focused on reducing the risk of heart conditions and morbidity and mortality in society, on improving the quality of life under the supervision of a multidisciplinary health team, triggering benefits in patients with cardiovascular diseases or who have undergone to a surgical intervention due to the implantation of an automatic defibrillator allowing to recover and maintain functional independence. The objective of this research project was to analyze the intervention of cardiac rehabilitation in patients with implanted cardioverter defibrillators and the positive effects of physical activity on musculoskeletal and cardiac physiology. This development was carried out under the bibliographic review modality, using scientific domain articles, which were extracted from databases such as Cochrane Library, Scielo, PubMed, Google Scholar, Science Direct, PEDro, and SJR, where 100 scientific articles They were selected preliminarily. After the assessment on the methodological scale of PEDro equal to or greater than 6 points, 35 were chosen for this study, which corresponds to clinical trials, which made it possible to demonstrate the importance of cardiac rehabilitation in patients with cardiovascular and post-surgical pathologies. Limits physical training and involves educational, nutritional, and psychological programs and control of risk factors for prolonged survival. Therefore, the contribution of the rehabilitation program in an adult with a defibrillator causes improvement in the strength and resistance of the body muscles, maintaining the physiological levels of blood pressure, heart rate, and oxygen saturation within normal parameters.